Multiscale Transforms with Application to Image Processing - Vyas, Aparna; Yu, Soohwan; Paik, Joonki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book provides an introduction to image processing, an overview of the transforms which are most widely used in the field of image processing, and an introduction to the application of multiscale transforms in image processing.   The book is divided into three parts, with the first part offering the reader a basic introduction to image processing. The second part of the book starts with a chapter on Fourier analysis and Fourier transforms, wavelet analysis, and ends with a chapter on new multiscale transforms. The final part of the book deals with all of the most important applications of multiscale transforms in image processing.  The chapters consist of both tutorial and highly advanced material, and as such the book is intended to be a reference text for graduate students and researchers to obtain state-of-the-art knowledge on specific applications. The technique of solving problems in the transform domain is common in applied mathematics and widely used in research andindustry, but is a somewhat neglected subject within the undergraduate curriculum. It is hoped that faculty can use this book to create a course that can be offered early in the curriculum and fill this void. Also, the book is intended to be used as a reference manual for scientists who are engaged in image processing research, developers of image processing hardware and software systems, and practising engineers and scientists who use image processing as a tool in their applications.
I Introduction to Image Processing -- 1 Fundamentals of Digital Image Processing -- II Multiscale Transform -- 2 Fourier Analysis and Fourier Transform -- 3 Wavelets and Wavelet Transform -- 4 New Multiscale Constructions -- III Application of Multiscale transforms to Image Processing -- 5 Image Restoration -- 6 Image Enhancement.- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Appendix E.- Index.
Keywords: Signal processing; Computer vision; Signal, Speech and Image Processing; Computer Vision